Kepuasan Konsumen Tidak Selalu Membentuk Loyalitas - Yuli Harwani (Jurnal Manajemen, 2017)
This study aims to understand the role of brand equity as a competitive advantage associated with the decision-making process in the selection of universities. The research method used in this research is descriptive method. The object of this research as many as 100 people in West Jakarta, especially in the area of Kembangan and Kebon Jeruk. The approach used in this research is Structural Equation Model (SEM) with Smart PLS analysis tool. The results showed that brand equity has a positive and significant impact on competitive advantage. Brand equity has a positive and significant impact on decision stability. However, competitive advantage shows no effect on decision making.